2012
DOI: 10.1136/bmj.e1717
|View full text |Cite
|
Sign up to set email alerts
|

Patient safety, satisfaction, and quality of hospital care: cross sectional surveys of nurses and patients in 12 countries in Europe and the United States

Abstract: Objective To determine whether hospitals with a good organisation of care (such as improved nurse staffing and work environments) can affect patient care and nurse workforce stability in European countries. Design Cross sectional surveys of patients and nurses.Setting Nurses were surveyed in general acute care hospitals (488 in 12 European countries; 617 in the United States); patients were surveyed in 210 European hospitals and 430 US hospitals.Participants 33 659 nurses and 11 318 patients in Europe; 27 509 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

63
1,442
10
87

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,588 publications
(1,679 citation statements)
references
References 23 publications
63
1,442
10
87
Order By: Relevance
“…None of the six studies that met our inclusion criteria showed significant associations between nurse staffing levels and nurse outcomes, although a number of other studies suggest that there are higher levels of job dissatisfaction and burnout amongst nurses where staffing levels are lower (e.g. Aiken et al, 2002, Aiken et al, 2012.…”
Section: Other Outcomesmentioning
confidence: 99%
“…None of the six studies that met our inclusion criteria showed significant associations between nurse staffing levels and nurse outcomes, although a number of other studies suggest that there are higher levels of job dissatisfaction and burnout amongst nurses where staffing levels are lower (e.g. Aiken et al, 2002, Aiken et al, 2012.…”
Section: Other Outcomesmentioning
confidence: 99%
“…Aiken (18) , studied 10,319 nurses from 303 hospitals and concludes that adequate staffing and administrative support were among the most important factors for improving the job quality for nurses and patient care. (25) The findings of this study are in accordance with the results reported by Zuzelo (26) and Epstein, (27) who investigated hospital nurses and their professional ethical dilemmas similar to Range&Rotherham (28) and Mattozinho& Freitas (29) stating that ethical issues caused emotional burden among nurses and led to attrition.…”
Section: Discussionmentioning
confidence: 99%
“…Results of this study are consistent with the growing body of published research providing evidence that nursing care has a direct effect on patient's health outcomes and the quality of nursing care is influenced by nurses' fatigue, frustration, low perception of care quality and lastly, planning to leave the profession. (18) Stress and tension at work lead to job dissatisfaction and attrition. In contrast, a positive work environment helps retention of nurses with adequate staffing and resources.…”
Section: Discussionmentioning
confidence: 99%
“…The Netherlands had the lowest percentage (10%) and in the USA 34% of nurses reported burnout (Aiken et al, 2012). Burnout can result in high staff turnover and absenteeism and can result in significant financial costs to organisations (Kedem & Bagan, 2005).…”
Section: Discussionmentioning
confidence: 99%